The effect of surgery started at different time point during the day on the clinical outcomes of mitral valve surgery - Zheng, Shuai; Wang, Jiangang; Zhang, Haibo; Wang, Shengyu; Meng, Xu (Frontiers in Cardiovascular Medicine, 2024)
The clinical prognosis of mitral valve surgery at morning, afternoon, and evening is not yet clear. The aim of the study is to investigate the impact of different time periods of surgery in the morning, afternoon and evening on the short-term and long-term results of mitral valve surgery.From January 2018 to December 2020, 947 patients with mitral valve surgery in our department were selected. These patients were divided into 3 groups according to the starting time of surgery. Morning group (operation start time 8:00-10:30, n=231), afternoon group (operation start time 12:00-14:30, n=543), and evening group (operation start time 17:30-20:00, n=173). The short-term and long-term results of the three groups were compared.There were no significant difference in the long-term mortality, long-term risk of stroke and reoperation. And there were no significant difference in in-hospital outcomes, including mortality, stroke, cardiopulmonary bypass time, aortic cross clamp time, mitral valve repair convert to mitral valve replacement, number of aortic cross clamp ≥2 times, unplanned secondary surgery during hospitalization (including thoracotomy hemostasis, thoracotomy exploration, redo mitral valve surgery, and debridement), intra-aortic balloon pump, extracorporeal membrane oxygenation, continuous renal replacement therapy, mechanical ventilation time, and intensive care unit length of stay.There is no significant difference in the risk of short-term and long-term survival and adverse events after mitral valve surgery at different time periods in the morning, afternoon, and evening. Mitral valve surgery at night is safe.